Pengaruh Model Pembelajaran Berbasis Penemuan Terhadap Motivasi dan Hasil Belajar Peserta Disik Kelas X MIA SMA Negeri 3Lau Maros (Studi Pada Materi Pokok Larutan Elektrolit dan Nonelektrolit) - Nurshafa Fadhilah; Sudding Sudding; Muharram Muharram (ChemEdu, 2020)
The research was a quasi-experimental that aimed to know the effect ofdiscovery learning model toward student’s motivation and achievement of class X MIA SMA Negeri 3 Lau Maros. The independent variable in this experiment was discovery learning model and the dependent variable were student’s motivation and achievement on electrolyte and nonelectrolyte solution subject matter. The population was class X MIA SMA Negeri 3 Lau Maros consisted of 180 students. Taking technique of sample was simple random sampling. The sample of this research consisted of two classes, namely class X MIA3 as a experiment class with 30 students and class X MIA2 as a control class with 30 students. The data of the research were gathered by motivation questionnaire and achievement testelectrolyte and nonelectrolyte solution subject matter for post-test which were analyzedby using t-test. Results of inferential statisticalanalysis for learning motivation were tcalculated =2.59>t(0,05;58)=1,67 and achievement were tcalculated =2.43>t(0,05;58)=1,67. Conclude that discovery learning model gives effected toward student’s motivation and achievement of class X MIA SMA Negeri 3Lau Maros on electrolyte and nonelectrolyte solution subject matter.